AL HALAJ SUFI MATI DALAM TIANG SALIB ( KAJIAN FILSAFAT BEBAS NILAI) - Taufiq . (LPPM Universitas Pekalongan, 2014)
Basically every man according to his nature acknowledge their authority beyond himself who created the universe and its contents, which is called God. Humans tried to describe the presence of God in his life according to the ability of thought, there is the God described in the form of sculpture, there is described a God, formless, intangible. In search of the God of the philosophers use a variety of methods, some use the method of Plato, Socrates, Al-Ghazali and so on. The philosophers have already reached the level of approach to God, such as Al-Halaj. Al-Halaj other philosophers as value-free, Al-Halaj a solid figure in the founding philosophers, so that he died in the gallow